2022
DOI: 10.1002/ehf2.14009
|View full text |Cite
|
Sign up to set email alerts
|

Association between trimethylamine N‐oxide and prognosis of patients with acute myocardial infarction and heart failure

Abstract: Aims This study aimed to investigate the association between trimethylamine N‐oxide (TMAO) and the prognosis and association between high‐sensitivity C‐reactive protein (hsCRP) and TMAO‐associated cardiovascular risk in patients with acute myocardial infarction (AMI) complicated by heart failure (HF). Methods and results A total of 985 patients presenting with AMI and HF were consecutively enrolled at the Fuwai Hospital between March 2017 and January 2020. Patients were stratified into groups according to tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In this context, in the present issue of the ESC Heart Failure journal, Li et al showed that elevated TMAO levels were associated with poor prognosis (i.e. all‐cause death and recurrence of myocardial infarction) in patients with acute myocardial infarction complicated by HF, 29 further validating current understanding 12,36 . Specifically, the authors found that patients with higher sensitivity C‐reactive protein (hsCRP) levels resulted in a further significant stratification of TMAO by tertiles for MACE.…”
Section: Figurementioning
confidence: 87%
See 3 more Smart Citations
“…In this context, in the present issue of the ESC Heart Failure journal, Li et al showed that elevated TMAO levels were associated with poor prognosis (i.e. all‐cause death and recurrence of myocardial infarction) in patients with acute myocardial infarction complicated by HF, 29 further validating current understanding 12,36 . Specifically, the authors found that patients with higher sensitivity C‐reactive protein (hsCRP) levels resulted in a further significant stratification of TMAO by tertiles for MACE.…”
Section: Figurementioning
confidence: 87%
“…Amongst the cardiovascular diseases, HF represents a widely investigated disease for association with the gut, with evidence available in both reduced (HFrEF) 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 and preserved (HFpEF) 22 , 23 , 24 , 25 , 26 , 27 phenotypes, as well as in acute 12 , 13 , 28 , 29 , 30 and chronic setting 9 , 10 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 (see Table 1 ). From a pathophysiological point of view, TMAO pathway affects HF in different ways.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A total of twelve studies on the dose-response relationship between circulating TMAO levels and the risk of hypertension in patients with CVD were included. [16][17][18][20][21][22][23]25,26,[28][29][30] The results of study quality revealed that the NOS scores of 3 studies were 7, [16,25,27] 6 studies had NOS scores of 8, [19,[21][22][23][24]29] and 6 studies had NOS scores of 9. [17,18,20,26,28,30] (the general characteristics of the included studies are illustrated in Table 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%